2020
DOI: 10.1186/s40164-020-00170-6
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia incidence trends at the global, regional, and national level between 1990 and 2017

Abstract: Background: Leukemias are a group of life-threatening malignant disorders of the blood and bone marrow. The incidence of leukemia varies by pathological types and among different populations. Methods: We retrieved the incidence data for leukemia by sex, age, location, calendar year, and type from the Global Burden of Disease online database. The estimated average percentage change (EAPC) was used to quantify the trends of the age-standardized incidence rate (ASIR) of leukemia from 1990 to 2017. Results: Global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
156
2
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(173 citation statements)
references
References 37 publications
6
156
2
9
Order By: Relevance
“…The incidence of hematologic malignancies varies based on subtypes, age, gender, and socioeconomic state. For instance, between 1990 and 2017, a notable decrease in acute lymphocytic leukemia (ALL) and chronic myeloid leukemia (CML) incidence was discovered; however, the incidence rate of chronic lymphocytic leukemia (CLL) and acute myeloid leukemia (AML) has considerably raised in most countries [ 5 ]. The incidence cases of HL increased 38.6% from 1990 to 2017 [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The incidence of hematologic malignancies varies based on subtypes, age, gender, and socioeconomic state. For instance, between 1990 and 2017, a notable decrease in acute lymphocytic leukemia (ALL) and chronic myeloid leukemia (CML) incidence was discovered; however, the incidence rate of chronic lymphocytic leukemia (CLL) and acute myeloid leukemia (AML) has considerably raised in most countries [ 5 ]. The incidence cases of HL increased 38.6% from 1990 to 2017 [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence cases of HL increased 38.6% from 1990 to 2017 [ 6 ]. Leukemia’s age-standardized incidence rate (ASIR) was higher in males compared to females [ 5 ]. Moreover, it has been revealed that the incidence of leukemia only has been increasing in people aged ≥ 70 years [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the key achievements obtained with novel biological agents developed during the last decade, leukemia remains an incurable disease [ 1 ]. One of the major challenges related to the treatment of leukemia is the huge diversity of these neoplasms [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%